Bartolomé Bennassar et le soutien institutionnel à la recherche sur l’Espagne moderne et contemporaine : L’aventure de la RCP 405 et du GDR 30 - Gérard Chastagnaret (Les Cahiers de Framespa)
This contribution aims to highlight one aspect of Bartolomé Bennassar's work, which was little known but decisive in his time for the advancement of research on early modern and modern Spain: his role in structuring research from the mid-1970s onwards. The creation, under his leadership, of two successive entities, an RCP and then a GDR, bringing together researchers from the universities of Toulouse II, Bordeaux IV, the University of Provence and the CNRS, made it possible to obtain the necessary funding and computing support to complete several “thèses d’État”. Bartolomé Bennassar thus played a dual role: he facilitated the early use of computer technology for data processing in the field of Social Sciences and Humanities, and he was a go-between, from individual doctoral research to collective research.